Pitfalls and potential of institutional change: Rain-index insurance and the sustainability of rangeland management - Birgit Müller; Martin Quaas; Karin Frank; Stefan Baumgärtner (Verein für Socialpolitik, 2010)
Rain-index insurance is strongly advocated in many parts of the developing world to help farmers to cope with climatic risk that prevail in (semi-)arid rangelands due to low and highly uncertain rainfall. We present a modeling analysis of how the availability of rain-index insurance affects the sustainability of rangeland management. We show that a rain-index insurance with frequent payoffs, i.e. a high strike level, leads to the choice of less sustainable grazing management than without insurance available. However, rain-index insurance with a low to medium strike level enhances the farmer's well-being while not impairing the sustainability of rangeland management.
Keywords: D81; G22; Q57; 330; ecological-economic modeling; weather-index insurance; Namibia; risk; weather-based derivatives; Africa